Membangun Karier Adaptif: Peran Keterampilan, Dukungan Teman, dan Efikasi Diri Keputusan Karier Siswa SMKN 1 Bendo Magetan: Building an Adaptive Career: The Role of Skills, Peer Support, and Self-Efficacy in Students' Career Decisions at SMKN 1 Bendo Magetan - Razan Ihtifazhuddan; Lilik Anifah; I Gusti Putu Asto Buditjahjanto (Edu Cendikia: Jurnal Ilmiah Kependidikan, 2024)
The low interest and ability of SMKN 1 Bendo Magetan students in "calculating" indicates a competency gap that can hinder future career prospects. In addition, the low inability of students to adapt and make the right career decisions after graduation suggests a gap in the career guidance system in schools. Based on these problems, the urgency of this study is to identify several fundamental challenges in student career development. This study aims to determine the effect of Technical Skill, Career Decision Self-Efficacy, and Peer Support as independent variables and Career Adaptability as the dependent variable. This type of research uses quantitative with a correlational approach. The study was conducted in the Construction and Housing Engineering Expertise Concentration of SMKN 1 Bendo Magetan with a population of 214 students. The sample in this study was 214 students using the Convenience Sampling technique. The data collection technique used a psychological scale, namely the Technical Skill scale, Career Decision Self-Efficacy and Peer Support, and the Career Adaptability scale, both in the form of a Likert scale. The findings show that technical skills, peer support, and career decision self-efficacy significantly and have a positive correlation affecting students' career adaptability. All three are competency constructs, not treatments. Each represents a different dimension in the development of individual potential. Technical skills, peer support, and self-confidence in career decision-making are essential determinants of career adaptability for students majoring in construction and housing engineering at SMKN 1 Bendo Magetan. The role of teachers is vital in improving aspects of students, one of which is career adaptability. In this case, teachers must also consider aspects outside student competency that can support student career adaptability. The researcher suggests that further research should examine other factors related to student career adaptability.